Effects of KNO3 concentration and aeration during seed priming on seed quality of wax gourd (Benincasa hispida [Thunb.] Cogn.) - Na nakorn, Ploypairin; Kaewsorn, Pichittra (Agriculture and Natural Resources, 2021)
Wax gourd seed has an extremely low germination rate and a high dormancy level. A laboratory experiment studied the effects of KNO3 concentration and aeration during seed priming to enhance the rate of germination and the germination percentage of wax gourd seed. A 3×2 factorial experiments in completely randomized design including non-primed seeds (control) was implemented, using factor A as the KNO3 concentration (0%, 3% or 5%) and factor B as either non-aeration or aeration. Seeds were soaked in a KNO3 solution for 72 hr at 30 ± 2°C; then, the seed moisture content was reduced to approximately 7%. Priming treatments were applied in four replicates of 50 seeds per replicate. The effects of the priming treatments were evaluated based on a comparative analysis of a standard germination test, days to emergence (DTE) and mean germination time (MGT) among the treatments. The results indicated that seed priming with 3% or 5% KNO3 solution with aeration had the greatest mean (± SD) germination rates (91.00 ± 3.83% and 95.00 ± 2.58%, respectively), the lowest DTE (3.63 ± 0.28 d and 3.70 ± 0.32 d, respectively) and the lowest MGT (10.60 ± 0.60 d and 10.42 ± 0.29 d, respectively) compared to those of non-primed seeds (40.00 ± 7.12% germination, 6.59 ± 0.38 d DTE and 13.67 ± 0.30 d MGT). Therefore, priming wax gourd seed with 3% or 5% KNO3 solution with aeration can be used to increase the speed of seed germination while simultaneously increasing the germination percentage.